Mrs. Lincoln's dressmaker [large type] : a novel - Chiaverini, Jennifer (Thorndike Press, 2013)
Presents a fictionalized account of the friendship between Mary Todd Lincoln and her dressmaker Elizabeth Keckley, a former slave.